Investments in Higher Education in OECD Countries - Beňová, Elena; Vališová, Dasa; Dubrovina, Vira (Inwestycje w szkolnictwie wyższym w krajach OECD, 2010)
The article deals with investments in higher education in the most developed countries in the world, which importance is growing especially in consequence of increasing interest in higher education. The issue of obtaining additional financial resources is relating to countries, in which the system of higher education is covered primarily through the public resources. These countries should think about a change in their system of financing higher education in the future (for example by the implementation of student’s financial participation on the costs allied to their education), because apart from that they might not be able to cover constantly increasing demand for higher education and also the increasing quality of higher education. This could consequently endanger their position in the international competition and also in the process of globalization.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 149, s. 31-38
Keywords: investments; higher education; benefits; OECD countries; expenditures